ROOT HAIR DEFECTIVE3 Is a Receptor for Selective Autophagy of the Endoplasmic Reticulum in Arabidopsis - Sun, Jiaqi; Wang, Weina; Zheng, Huanquan (Frontiers in Plant Science, 2022)
ROOT HAIR DEFECTIVE3 (RHD3) is a plant member of atlastin GTPases, which belong to an evolutionally conserved family of proteins that mediate the homotypic fusion of the endoplasmic reticulum (ER). An atlastin in mammalian cells has recently been shown to act as an ER-phagy receptor for selective autophagy of the ER (ER-phagy) during nutrient starvation. Although RHD3 has been indicated to play a role in ER stress response, it is not very clear how RHD3 is involved in the process. Here we showed that the rhd3 mutant is hyposensitive to ER as well as salt stress. We employed a YFP tagged ER membrane marker YFP-TMC to monitor the efficiency of ER-phagy microscopically and biochemically. We found that rhd3 is defective in ER-phagy under ER stress. Furthermore, there is an increased association of YFP-RHD3 with ATG8e-marked autophagosomes. YFP-RHD3 is also visible with ATG8e in the vacuole and there is a breakdown of YFP-RHD3 under ER stress. RHD3 has two putative ATG8 interaction motifs (AIM1-2). We revealed that RHD3, but not RHD3(ΔAIM1) physically interacts with ATG8, a core autophagosomal component that interacts with various receptor proteins to recruit cargos for degradation by selective autophagy. Furthermore, their interaction is enhanced under ER stress. We thus propose that RHD3 acts as an ER-phagy receptor under ER stress to promote selective autophagy of the ER in Arabidopsis.